PERBEDAAN HASIL BELAJAR ANAK DENGAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER (NHT) DAN PEMBELAJARAN KONVENSIONAL DI KELAS VIII MTs. AL-MUKHTARIYAH SUNGAI DUA KEC. PORTIBI KAB. PADANG LAWAS UTARA - Sry Wirna Cahlida; Nasrul Syakur Chaniago (AXIOM : Jurnal Pendidikan dan Matematika, 2016)
The purpose of this study was to determine differences Children WithLearning Outcomes Cooperative Learning Model Numbered HeadTogether (NHT) and Conventional class VIII MTs Al-MukhtariyahTwo Rivers district. Portibi Kab. North Padang Lawas. This research isquantitative, with a kind of experimental research. The population is theentire class VIII MTs Al-Mukhtariyah Sungai Dua and the sample areall children of class VIII MTs Al-Mukhtariyah Two Rivers district.Portibi Kab. North Padang Lawas totaling 48 people because theschools there are only two classes. Data analysis is the analysis ofvariance (ANOVA). These findings show: the learning outcomes ofchildren with cooperative learning model Numbered Head Together(NHT) by the end of the test scores obtained rata73,6 mean value andstandard deviation of 7.708. While the learning outcomes of childrenwith pemebelajaran Conventional models based on the final test scoresgained an average of 68.75 and a standard deviation of 6.124. Based onstatistical calculation t-test for children's learning outcomes obtainedthitung > ttabel, then the hypothesis is Ha rejected and H0 accepted, whichmeans that there are differences in learning outcomes in children givencooperative learning NHT type and conventional learning. ConclusionsThis study explains that children learn better outcome using cooperativelearning model Numbered Head Together (NHT) of the Conventionalmethod Class VIII MTs Al-Mukhtariyah Two Rivers district. PortibiKab. North Padang Lawas.